Model Manajemen Dakwah Transformasional Berbasis Nilai: Analisis Program Kafilah Du’at PERSIS 2022–2027 - Siti Shobriyah Hawasy; Ayu Ariska; May Putri Wulandari; Yusuf Zaenal Abidin (FDIK IAIN Padangsidimpuan, 2026)
This study aims to analyze the da’wah management system applied by Persatuan Islam (PERSIS) using the classical management theory of POAC (Planning, Organizing, Actuating, Controlling) and the transformational leadership model. Employing a descriptive qualitative approach through document study, this research examines official documents such as Rencana Jihad 2022–2027, SK Tasykil, and Kurikulum Tamhidul Mubalighin as primary data representing the patterns of planning, implementation, and evaluation of da’wah management. The findings indicate that PERSIS does not only adopt modern managerial principles but also integrates spiritual and social values into its institutional practices. The flagship program Kafilah Du’at serves as a concrete manifestation of transformational leadership in da’wah, inspiring social change, strengthening cadre development, and fostering humanistic values. This study concludes that effective contemporary da’wah requires a value-based systemic approach where adaptive organizational structures and outcome-oriented strategies align with the institution’s spiritual ideals. The findings contribute to developing a paradigm of transformational value-based da’wah management in Indonesia’s plural and dynamic Islamic context.